Anesthetic management of cesarean section in parturients with severe mitral stenosis: A case series - Kirti N Saxena; Bharti Wadhwa; Devika Mishra (Wolters Kluwer Medknow Publications, 2019)
Mitral stenosis (MS) is the most common valvular heart disease associated with pregnancy. The increase in cardiac output during pregnancy results in deterioration of the patient's condition with progress to higher New York Heart Association class. Both general and regional anesthesias have been described for cesarean section in these patients. Anesthetic management of these patients depends upon the severity of the disease. General anesthesia has traditionally been preferred for cesarean section in patients with severe MS. Regional anesthesia has become popular as a safe choice in the recent past for cesarean section in all parturients including those with heart disease. We report three parturients with severe MS who underwent cesarean delivery under graded epidural block successfully. The parturients and the neonates were fine after the procedure.